Ammonia-induced precipitation of zirconyl chloride and zirconyl-yttrium chloride solutions under industrially relevant conditions - Carter, Geoffrey; Ogden, Mark; Buckley, Craig; Maitland, Clinton; Paskevicius, Mark (Elsevier, 2008)
The influence of concentration and added chloride salts on the solution speciation of zirconyl chloride solutions, and the precipitate formed upon addition of aqueous ammonia, has been investigated. Crystalline zirconium oxychloride octahydrate samples available on an industrial scale were investigated using ICP-OES, XRD and SEM. The samples had a remarkably consistent level of the trace elements and LOI and contained approximately 2 wt.% hafnium. Zirconyl chloride solutions at industrially relevant concentrations of 0.81 and 1.62 M were studied by small angle X-ray scattering, and the particle radii were found to be unchanged within experimental error. Yttrium–zirconium mixed solutions relevant to the Solid Oxide Fuel Cell market (containing 3, 5, 8 and 10 mole% yttrium) were also investigated, and it was found that the added yttrium did not significantly change the particle radii or particle-particle distances.Solutions at the same concentrations were then precipitated using a continuous double jet precipitation apparatus with aqueous ammonia as the base. Using DLS it was found that the zirconyl chloride solution at higher concentration yielded a larger precipitated particle size (1.0 ± 0.1 μm, 4.2 ± 0.1 μm). The yttrium–zirconium mixed solutions were found to give a consistent increase in particle size with increasing yttrium levels (2.0 ± 0.1 μm, 3.7 ± 0.2 μm, 4.5 ± 0.1 μm and 4.9 ± 0.2 μm). To investigate if the growth effect was most influenced by the cations or the increasing chloride concentrations, sample solutions containing mixtures of caesium chloride/zirconyl chloride and calcium chloride/zirconyl chloride with the same concentration of added chloride anions as that of the 8 mole% yttrium–zirconium sample were precipitated. The increased particle size was found to be most dependent on the type of cation and did not appear to be as significantly dependent on the concentration of chloride ions.